Religious Institutions as Global Sustainability Champions: Istiqlal Mosque’s Green Mosque Program and the Sustainable Development Goals - Farabi, Nadia; Tri Fatharini, Anjani (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2025)
This study examines the Istiqlal Mosque in Jakarta—Indonesia’s national mosque and the first mosque in the world to receive EDGE green building certification in 2022—as an example of how a religious institution can engage with global sustainability agendas. While the mosque’s technical improvements in energy and water efficiency contributed to its recognition, this study focuses on how Istiqlal integrates environmental responsibility into its religious authority, institutional practices, and community outreach. By analyzing the mosque’s programs on resource management, environmental education, and public engagement, the study shows how Istiqlal contributes to several Sustainable Development Goals (SDGs 6, 7, 11, 12, and 13) in ways grounded in Islamic ethical principles such as stewardship, balance (mīzān), and the avoidance of harm. The article argues that Istiqlal demonstrates how a domestic religious institution can interpret, translate, and localize global sustainability norms in ways that are culturally grounded and institutionally actionable. In doing so, the study contributes to broader debates on the role of religious actors in global governance and the institutionalization of Islamic environmental ethics in contemporary Southeast Asia.